Ho-Chunk materials, ACLS collection - Blowsnake, Sam; Boas, Franz, 1858-1942; Marsh, Gordon H.; Susman, Amelia, 1915- (1938)
The Ho-Chunk materials in the ACLS collection consists primarily of three items in the "Winnebago (Ho-Chunk)" section of the finding aid. The bulk of the material is Amelia Susman's 11 field notebooks, which contains texts with interlinear translation, Vocabularies, ethnographical and linguistic notes, and some songs. Two additional items also by Susman are extended analyses based upon field work with Sam Blowsnake and wife: "The accentual system of Winnebago" and "The Winnebago syllabary." In the "Chiwere (Iowa)" section of the finding aid, Gordon Marsh's "Materials for a study of the Iowa Indian language" include some Ho-Chunk grammatical notes, and Ho-Chunk cognates with Chiwere. Lastly, in the "Dakota" section, Franz Boas' "Miscellaneous Dakota notes" (item X8a.3) includes a Dakota-Ho-Chunk comparative word list.